AGROCLIMATIC IMPACTS FOR AGRICULTURAL CROPS IN THE STATE OF PARAÍBA UNDER CONDITIONS OF CLIMATE CHANGE - Fernandes Cândido, Amanda; de Sousa Nascimento, Robson; Peixoto Borges, Valéria (Revista Brasileira de Engenharia de Biossistemas, 2021)
The aim of the present work was to perform an agroclimatic zoning for the Paraíba State, Brazil taking as basis the climate change scenarios of the Intergovernmental Panel on Climate Change (IPCC), to assess the impact of water demand on the production of sugarcane, corn and rice, identifying and quantifying the areas that are suitable, unfit or that have some restrictions for these cultivations. The climatological water balance and the humidity index were determined using meteorological data of pluviometric precipitation and average air temperature of the six stations contained in the state, referring to the period from 1981 to 2018. To determine the agroclimatic ability of the crops, the humidity index ranges were used. It was found that in the normal scenario about 7.6% and 10% of the state’s area has full suitability without restrictions and full suitability with prolonged rainy season, respectively, for the three crops. In an optimistic scenario, 7% of the state’s area has moderate suitability due to water deficiency and 93% inept due to water deficiency. In a pessimistic scenario, the cultivation of crops in the state is not viable due to the drastic reduction in water availability for the region. It shows how much climate change can economically impact the Paraíba State, and mitigation policies must be created.